Impact of project simulation shareholding incentive on team performance: Research based on the construction industry - ZHOU, Jian (Institutional Knowledge at Singapore Management University, 2024)
China's construction industry is vast and possesses a wide market; however, it faces challenges such as unclear stratification and low concentration levels. Construction enterprises face significant constraints in key areas such as financial strength, team stability, and technological advancement, while also bearing substantial costs related to supervision and accountability. The project simulation shareholding mode enhances employees' sense of belonging and responsibility through a collaborative approach characterized by joint management, shared risks, and shared benefits. This improves project execution efficiency and quality, ultimately strengthening the core competitiveness of the enterprise. In the construction industry, projects often involve substantial investments and long-term collaboration, making internal harmony and cooperation within the team crucial for the project's success. The project simulation shareholding incentive can effectively address agency problems and reduce conflicts between individual and team interests, thereby promoting team coordination and enhancing project performance. This study focuses on the challenges of project team management in the private construction industry. It aims to explore the moderating role of the key process mechanism (team coordination) and situational factor (relational closeness with platform companies) in the impact of the project simulation shareholding mode on project team performance (safety performance and financial performance). This study comprehensively considers the equity structure among internal team members within construction industry project teams as well as the funding ratio between the project team and the group company. It analyzes the impact mechanism of the project simulation shareholding mode on team performance, with a focus on its effects on key performance indicators such as the project team's cash flow, project duration, cost, quality, compliance, safety, trust and respect, effective communication, and team cohesion. This study uses a questionnaire survey to gather statistical data to examine the construction projects of non-listed construction enterprises in Jiangsu and Zhejiang. The empirical statistical analysis method tests the proposed model and hypotheses based on the collected data. The findings reveal that the project simulation shareholding mode positively affects team safety and financial performance by enhancing team coordination. Additionally, the relational closeness with the platform company moderates the indirect effect of the project simulation shareholding mode on team safety and financial performance through team coordination.